Appearance of untreated bone metastases from breast cancer on FDG PET/CT: Importance of histologic subtype - Dashevsky, Brittany Z. (Eur J Nucl Med Mol Imaging, 2015)
PURPOSE: Determine if the histology of a breast malignancy influences the appearance of untreated osseous metastases on FDG PET/CT. METHODS: This retrospective study was performed under IRB waiver. Our Hospital Information System was screened for breast cancer patients who presented with osseous metastases, who underwent FDG PET/CT prior to systemic therapy or radiation from 2009–2012. Patients with invasive ductal carcinoma (IDC), invasive lobular carcinoma (ILC), or mixed ductal/lobular (MDL) histology were included. Patients with history of other malignancies were excluded. PET/CT was evaluated, blinded to histology, to classify osseous metastases on a per patient basis as sclerotic, lytic, mixed lytic/sclerotic, or occult on CT, and record SUVmax for osseous metastases on PET. RESULTS: 95 patients met inclusion criteria (74 IDC, 13 ILC, and 8 MDL). ILC osseous metastases were more commonly sclerotic and demonstrated lower SUVmax than IDC metastases. For all IDC and MDL patients with osseous metastases, at least one was FDG-avid. For ILC, all patients with lytic or mixed osseous metastases demonstrated at least one FDG-avid metastasis; however, only 3 of 7 patients with sclerotic osseous metastases were apparent on FDG PET. CONCLUSIONS: The histologic subtype of breast cancer affects the appearance of untreated osseous metastases on FDG PET/CT. In particular, non-FDG-avid sclerotic osseous metastases were more common in patients with ILC, than in those with IDC. Breast cancer histology should be considered when interpreting non-FDG-avid sclerotic osseous lesions on PET/CT, which may be more suspicious for metastases (rather than benign lesions) in patients with ILC.